Application of Mohuntingo Philosophy as a Joint Protection of Children Victims of Violence (Study of Child Decent Cities in Gorontalo City) - Darmawati, Darmawati Darmawati; Arpin, Arpin Arpin; Sulaiman, Yana Yanti (Al-'Adl, 2024)
Sexual violence against children is part of a humanitarian emergency. Sexual violence continues to increase significantly, and even the relatives (family) of the perpetrators of sexual violence are part of the perpetrators of this violence. The research objective of this study is to reveal the role and involvement of local Mohuntingo traditions as a pathway to approach and resolve cases of sexual violence. This research method is descriptive-qualitative by providing descriptive descriptions related to sexual violence experienced by children. The results of this research show that the first several fundamental components, the involvement of the Mohuntingo tradition as a part of resolving sexual violence, are not accommodated properly, so the tradition ends up in the ritual aspect. Second, the government's policy of minimizing the practice of sexual violence against children is still passive, and the protection process is institutional-based. Mohuntingo's involvement is an uninvolved approach due to the government waiting for the results of complaints from people who have experienced sexual violence, so in reducing sexual violence, the involvement of Mohuntingo's approach is important to accommodate community participation.